Spatially resolved properties of early-type group-dominant galaxies with MUSE: gas content, ionization mechanisms, and metallicity gradients. Issue 4 (8th September 2022) - Lagos, P; Loubser, S I; Scott, T C; O'Sullivan, E; Kolokythas, K; Babul, A; Nigoche-Netro, A; Olivares, V; Sengupta, C
ABSTRACT: With the goal of a thorough investigation of the ionized gas and its origin in early-type group-dominant galaxies, we present archival MUSE data for 18 galaxies from the Complete Local-Volume Groups Sample (CLoGS). These data allowed us to study the spatially resolved warm gas properties, including the morphology of the ionized gas, EW(H α), and kinematics as well as the gas-phase metallicity (12 + log(O/H)) of these systems. In order to distinguish between different ionization mechanisms, we used the emission-line ratios [O iii ]/H β and [N ii ]/H α in the BPT diagrams and EW(H α). We find that the ionization sources in our sample have variable impacts at different radii; central regions are more influenced by low-luminosity active galactic nuclei, while extended regions of low-ionization nuclear emission-line region-like emission are ionized by other mechanisms with post-asymptotic giant branch stars photoionization likely contributing significantly. We classified our sample into three H α +[N ii ] emission morphology types. We calculate the gas-phase metallicity assuming several methods and ionization sources. In general, 12 + log(O/H) decreases with radius from the centre for all galaxies, independently of nebular morphology type, indicating a metallicity gradient in the abundance profiles. Interestingly, the more extended filamentary structures and all extranuclear star-forming regions present shallow metallicity gradients. Within the uncertainties these extended structures can be considered chemically homogeneous. We suggest that group-dominant galaxies in our sample likely acquired their cold gas in the past as a consequence of one or more mechanisms, e.g. gas-clouds or satellite mergers/accretion and/or cooling flows that contribute to the growth of the ionized gas structures.